Does length of time between cases affect resident operative time for tonsillectomy and adenoidectomy?. (March 2022) - Shaikh, Noah; Tumlin, Parker; Morrow, Vincent; Bulbul, Mustafa G.; Coutras, Steven
Abstract: Objective: To evaluate the effect of prolonged time intervals between tonsillectomy and adenoidectomy (TA) on resident operative time and complications. Study design: Retrospective cohort. Setting: Tertiary academic hospital. Methods: This retrospective study covers a five-year period from 2015 to 2020. Time intervals between isolated pediatric TA cases performed by eight otolaryngology residents were reviewed to assess effect on operative time (defined as prolonged if ≥ 30 min and non-prolonged if < 30 min). Intervals including a procedure involving either a tonsillectomy or adenoidectomy that was a non-isolated TA were excluded. Results: A total of 309 isolated TAs were identified with 67.3% of procedures performed under 30 min. The mean surgical time interval between procedures was 5.83 ± 10.02 days (range 0.02–69.82). Most TAs were performed on patients aged 7 years or younger. Surgical time interval between TA was not a significant factor in determining prolonged operative time on univariable logistic regression, OR 1.01 (CI: 0.98 to 1.03) (p = 0.63). Patient age at surgery, adenoid grade, tonsil size and total number of TAs performed to date were significant factors in determining prolonged operative time in both univariable and multivariable logistic regression models. Prolonged operative time did not have a significant effect on readmission, reoperation, or post-operative bleeding. Conclusion: Extended time interval (up to 3 months) between routine TA does not affect operative time. Expansion of our methodology to more complex cases would be beneficial in designing resident training curriculum. Highlights: Time length between procedural tasks influences skills retention. Time interval between TA cases does not lead to prolonged operative time. Prolonged operative intervals and time in TA does not increase complications.